Dionysus Chooses Aeschylus - Larisa Poplavskaya (Hypothekai, 2018)
This article is devoted to the analysis of the early stage work of one of the first tragedians of the Greek theatre. Aeschylus is called the father of tragedy since he transformed the original theatrical performance with one actor and the cantata choir, released solemn choral lyric poetry from the dithyrambic genre to a fullfledged drama. Aeschylus was first to realize the importance of a dramatic conflict for the show on the stage of the heroic mythical legends. He introduced a second actor to make this show possible. The dramatic conflict was initiated and resolved in front of the audience, involved them in the action. Aeschylus gave the audience the possibility of empathy to heroes of the tragedy in their thoughts and doubts before they act the way it was known from the mythical stories. The title of the article when Aeschylus was chosen by God Dionysus to whom the plays were devoted on the Great Dionysus feast in Athens, proceeds from the comedy of Aristophanes “The Frogs.” This Comedy is considered to be the first experience of literary criticism in Ancient Greece. In the agon of the comedy, Aeschylus and Euripides are in Hades, the realm of the dead, and are competing for the right to be the first Greek tragedian. Dionysus is concerned about the lack of the theatrical repertoire at his feast since the great tragedians have already died. He descends into Hades to bring back the soul of Euripides but gives the primacy to Aeschylus and chooses him. Dionysus recognizes the educational significance of his tragedies “The Persians” and “Seven against Thebes”. The heroism and patriotism of the tragedies of Aeschylus are necessary for citizens of the Polis. The address to the comedy of Aristophanes is caused by a quotation from it in the anonymous biography of Aeschylus in his manuscripts. The biographer lists the merits of this playwright in the development of the Attic theater and leads the words of Dionysus to Aeschylus calling him “the first of the Hellenes” (Aristophanes “The Frogs”, 1004–1005). According to Dionysus as a hero of the comedy as well as the choice of Aristophanes, the tragedy of Aeschylus expresses the moral values of a generation of Athenians who defended the independence of the Motherland during the GreekPersian war. For this generation of citizens, the idea of kindness and justice has the enduring value and is sanctioned, as the Greeks believed, by the gods. The author focuses on one of the earliest tragedies of Aeschylus “The Suppliants”. The conflict of the drama lies in the choice of the position of the main hero Pelasgos, king of Argos, whether he should defend king Danaus’ daughters from the claims of their suitors. The article examines various versions of the mythical story of Io wanderings and the fate of the Danaides. The author analyzes lexical and poetic means used in choral parties of this tragedy. Aeschylus in the image mode leans on the poetics and stylistics of dithyrambic cantatas. In choral songslaments of the Danaides, he uses tunes of birds and intertwines them with wellknown myths about the transformation of heroes into different birds. In the poetics of Aeschylus, the seascape motives are presented. Since the early tragedy has still few opportunities to show the action, Aeschylus actively involves stichomythia when the characters say one or two poems. This method creates expression and tension, accelerates the action of the tragedy. Namely in his early tragedies, more closely related to the Greek choral lyric, the tragedian chooses true poetic means to create an image of the hero and thereby lays the foundations for the drama theatre of Ancient Greece as the future theatre of Europe.